Risks and Benefits of Global Warming and the Loss of Mountain Glaciers and Ice Patches to Archeological, Paleoclimate, and Paleoecology Resources - Brunswig, Robert H. (Ecological Questions, 2015)
Scientific documentation of global warming, despite disagreement on its ultimate causes, includes measurable rises in sea levels, more frequently stronger and more violent weather patterns, and accelerating melting of Arctic and Antarctic ice sheets, long-existing glaciers, and “permanent” snow fields. In recent years, there have been numerous discoveries of ancient human, animal, and plant remains melted from long-frozen snow and ice, finds which recently led to development of a new subfield of archaeology known as ice patch or glacial archaeology. Ice patch organic remains, once exposed, are subject to rapid deterioration and destruction. Both cultural and natural remains, if identified and collected prior to extended surface exposure can provide extraordinary evidence about past societies, climates, and ecosystems. This article provides a short background and discussion on the nature and history of the emerging science of glacier/ice patch archaeology and describes results of an on-going study in the United States’ southern Rocky Mountains where ice patch evidence for climate change is integrated with more traditional paleoclimate and archaeological research to reconstruct several millennia of cultural, climate, and ecological landscape evolution.